AIFM1‐associated X‐linked spondylometaphyseal dysplasia with cerebral hypomyelination. Issue 4 (13th January 2021) - Edgerley, Katharine; Barnicoat, Angela; Offiah, Amaka C.; Calder, Alistair D.; Mankad, Kshitij; Thomas, Nicholas Simon; Bunyan, David J.; Williams, Maggie; Buxton, Chris; Majumdar, Arniban; Vijayakumar, Kayal; Hilliard, Tom; et al.
Abstract: Spondylometaphyseal dysplasia with cerebral hypomyelination (SMD‐H) is a very rare but distinctive phenotype, unusually combining spondylometaphyseal dysplasia with hypomyelinating leukodystrophy. Recently, SMD‐H has been associated with variants confined to a specific intra‐genic locus involving Exon 7, suggesting that AIFM1 plays an important role in bone development and metabolism as well as cerebral myelination. Here we describe two further affected boys, one with a novel intronic variant associated with skipping of Exon 7 of AIFM1 and the other a synonymous variant within Exon 7 of AIFM1 . We describe their clinical course and radiological and genetic findings, providing further insight into the natural history of this condition.